An estimated DSGE model with financial accelerator: The case of Tunisia - Hager Ben Romdhane (Graduate Institute of International and Development Studies, 2020)
This paper estimates an open economy DSGE model with financial accelerator à la Bernanke et al. (1999)2, enriched with wage rigidities and imperfect exchange rate pass through. The objective of this paper is to assess the importance of financial frictions and their role in the transmission of transitory shocks in the Tunisian Economy. The model is estimated by Bayesian technics via Metropolis Hasting algorithm. Using Tunisian data, we obtain an estimate for the external risk premium, indicating the importance of the financial accelerator and the potential balance sheet vulnerabilities for macroeconomic fluctuations. Furthermore, results of the impulse responses functions model support that the inclusion of the financial accelerator magnifies the impact of shocks thereby increasing real fluctuations.
Keywords: 330; DSGE; Financial frictions; Bayesian estimation